Luz, câmera e chapéu de couro: a representação do cangaço nos filmes de Glauber Rocha e Carlos Coimbra - Silva, Juliana Alves da (2023)
The movement of the cangaço (1870-1940) is still present, as a theme, in several audiovisual productions. This research intends to discuss the representations of cangaço in Brazilian cinema, using as an object of analysis two films of the 1960s: “Lampião, o Rei do Cangaço” (1963), by Carlos Coimbra, and “Deus e o Diabo na Terra do Sol” (1964), by Glauber Rocha. Such films influenced the representations and conceptions of cangaço in subsequent productions, assisting in imagery conceptions of sertão, of the Northeast and northeastern